Impact of optimizing stroke green channel on treatment efficiency of acute ischemic stroke treatment efficiency in a county hospital - Yao WANG; Lei SHI; Guangbu LI; Qiyun ZHU; Xiaoqiang WU; Maolin LU; Haiyang LIN; Wei QI; Wei GAO; Ruiyin ZHOU; Qifeng LU; Baodong WU (Zhongguo Linchuang Yixue)
ObjectiveTo evaluate the impact of optimizing the stroke green channel on the efficiency of acute ischemic stroke management in a county hospital. MethodsA retrospective analysis of the emergency stroke green channel treatment data from Sixian People’s Hospital from May 2020 to April 2021 (before optimization of the green channel) and from May 2021 to April 2022 (after optimization of the green channel) was conducted. The rates of intravenous thrombolysis (IVT) and mechanical thrombectomy (MT) patients, as well as door-to-needle time (DNT), door-to-puncture time (DPT), and the modified Rankin scale (mRS) scores of patients three months post-treatment before and after the optimization of the stroke green channel were compared. ResultsWithin one year before and after optimization of the green channel, the number of acute visits for ischemic stroke was 3 143 and 2 623, respectively. Before optimization, 84 and 51 underwent IVT and MT, respectively. After optimization of the green channel, the ratios of patients underwent IVT (n＝215) and MT (n＝103) significantly increased, and both DNT and DPT were significantly shortened (P＜0.000 1); the proportion of MT patients with an mRS score of 0-2 at 3 months post-discharge significantly increased (46/99 vs 13/46, P＝0.038). ConclusionAfter optimizing the green channel at Sixian People’s Hospital, the efficiency of stroke treatment has significantly improved, and the patients’ prognosis improved.